Prosodic Characteristics of Semi-Spontaneous Speech - Olena Bialyk (Психолінгвістика, 2018)
The present article analyses the idea of semi-spontaneous speech, comparing it to spontaneous and prepared types of speech; studies and describes the prosodic characteristics of semi-spontaneous speech, implemented in the genre of interview; studies the role of speaker’s level of preparedness to the communication act in respect of prosodic speech behaviour and differentiates proportion of the preparedness in spontaneous, prepared and semi-spontaneous speech; distinguishes a specific genre of mass media discourse  – “star interview”, its structure and differential features, designating the role and functions of the interviewer in “speaker – interviewer – target mass audience” link. The studied material involves audio recordings of interviews with three popular British musicians: Phil Collins, Sting and George Michael. Separate monological statements taken from interviews were analyzed with a particular focus on prosodic characteristic, taking into consideration the matters under discussion, the speaker’s wish to elaborate upon a theme or shunt the conversation on another topic. Auditorial and acoustic analyses covered the research of such prosodic parameters as: the nature of the intonational scale, terminal tone and pausation peculiarities in the speakers’ speech. The central focus of the present research is on differentiation elements that characterize semi-spontaneous speech. The article describes essential aspects that have influence over the main prosodic characteristics of oral speech: experience in public speaking, individual characteristics of the speaker, physical and mental state, awareness of the topic discussed, desire to cover particular issues.